2010
DOI: 10.1590/s1517-70762010000200012
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic-mechanical behavior of epoxy matrix composites reinforced with ramie fibers

Abstract: The exceptional tensile strength of ramie fiber has motivated investigations on its application as reinforcement in polymeric composites. In this study the temperature variation of the dynamic-mechanical parameters of epoxy matrix composites incorporated with up to 30% in volume of ramie fiber were investigated by DMA tests. The parameters were the storage modulus, loss modulus and tangent delta. The investigation was conducted in the temperature from 20 to 200°C in an equipment operating in its flexural mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
40
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 13 publications
7
40
0
1
Order By: Relevance
“…[10][11][12][13][14][15][16][17][18][19] The statistical distribution of diameters was based on 100 randomly picked fibers from the lots. For each type of fiber overviewed in the PW, histograms corresponding to the frequency of diameter distribution were obtained [10][11][12][13][14][15][16][17][18][19] and reproduced in Figure 3. Diameters and cross-sectional areas along the fiber length were evaluated by means of profile projector measurements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12][13][14][15][16][17][18][19] The statistical distribution of diameters was based on 100 randomly picked fibers from the lots. For each type of fiber overviewed in the PW, histograms corresponding to the frequency of diameter distribution were obtained [10][11][12][13][14][15][16][17][18][19] and reproduced in Figure 3. Diameters and cross-sectional areas along the fiber length were evaluated by means of profile projector measurements.…”
Section: Resultsmentioning
confidence: 99%
“…[8] For palmirah fibers, the strength and the elongation decreased with the test length. [9] Recent works [10][11][12][13][14][15][16][17][18][19] have shown that not only pineapple but also many LCF species display an inverse correlation between the fiber diameter and its tensile strength. This appears to be a common feature to all fibers owing to the role played by microstructural defects and an intrinsic statistical distribution of microfibril strength.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of fibers can be applied as reinforcement, including cotton, flax, hemp, ramie, sisal, jute, banana, bamboo, curaua and buriti [1][2][3][4][5][6][7] . Actually, ramie textile applications have been replaced by synthetic fibers, mainly in clothes 2 . So, the motivation of this work is to study ramie fiber as composite reinforcement, with the concern to, in the future, maintain the culture of the fiber in the country.…”
Section: Introductionmentioning
confidence: 99%
“…(%)) 9 . In relation to mechanical properties, Margem et al 2 reported that the exceptional tensile strength of ramie fiber (in comparison with other natural fibers) has motivated researches on its application in polymer composites.…”
Section: Introductionmentioning
confidence: 99%